(untitled) (Communication & Society, 2018)
The goal of the present study is to broadly reconstruct the international debate on the cultural industry, from its origins to today. In particular, the links with other related concepts (creative industries and digital platforms) will be highlighted. The article is divided in three sections: the first reconstructs the origin of the concept, from the 1930s and 1940s, highlighting the theoretical heritage of Adorno and Horkheimer and, more generally, the scholars of the Frankfurt School. Together with Marcuse, those scholars identified, on the one hand, the consonances between industrial mass production and new forms of culture production and, on the other, formulated a radical critique of this change. In the same years in which the theories of this school were disseminated, Morin proposed a less pessimistic view of the same transformation. In the second section, the evolution of the concept of cultural industry during the end of the 1970s and the beginning of the 2000s is studied. During this period, the classical theories –after a phase of partial obscurity– were taken up. On one hand a socio-historical perspective emphasized the role played by national industries in shaping contents and styles. On the other hand, a series of scholars enlarged the definition to the creative industries. In the third section, some hypothesis are built about the evolution of the digital platforms and their links with the traditional definition of cultural industry.